Thermoelectric properties and EPR analysis of Fe doped Cu12Sb4S13 - GÜLER, ADİL; OKAY, CENGİZ; BOYRAZ, CİHAT (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
Recently tetrahedrite compounds have attracted great attention due to their potential applications on the mid temperature thermoelectric technologies. In this work, structural, Electron Paramagnetic Resonance (EPR) and the thermoelectric properties of tetrahedrite (Cu12-xFexSb4Si13 where x = 0.0, 1.0, 1.5, 2.5) were investigated. The crystal structural, morphological properties and elemental compositions of the samples were investigated by powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS-EDX) tools respectively. Magnetic properties of the samples were performed by EPR techniques using electron spin resonance (ESR) spectrometer with the model of Bruker EMX series at X-band (9.5 GHz). The thermoelectric properties were assisted based on Seebeck coefficient, electrical resistivity, and thermal conductivity measurement between 300 and 600 K temperature range. PXRD patterns and SEM-EDX analysis confirmed the main phase of tetrahedrite structure for all compounds. The Seebeck coefficient sign indicated that holes were dominant carriers in all compounds. Electrical resistivity measurement showed an increment with increasing Fe concentration likely due to decreasing in carrier density. A typical behavior of intrinsic semiconductor was observed from temperature-dependent electrical resistivity measurements. The maximum ZT value of 0.6 was achieved for the sample Cu11Sb4S13 at 550 K. Electron Paramagnetic Resonance (EPR) and thermoelectric measurements exhibited that the maximum Fe concentration might be 5 1.0 for achieving high ZT value in Cu12-xFexSb4Si13 compounds.
Keywords: Doped tetrahedrites; EPR properties; Thermal conductivity; Seebeck coefficient; Fe doped tetrahedrites; TETRAHEDRITE; PERFORMANCE; FIGURE